Ten Items to Find Them All: Shortening Scales for the Screening of Executive Function in Children With Attention Deficit/Hyperactivity Disorder. - Blasco-Fontecilla, Hilario; Bella-Fernández, Marcos (Actas Espanolas de Psiquiatria, 2025)
Background: Attention Deficit/Hyperactivity Disorder (ADHD) is the most common neurodevelopmental disorder. The affectation of executive functions is stressed in the most recent research on ADHD, and many tests are used to assess it in ADHD, but they are usually time- and effort-consuming. Methods: From a database of a total of 222 children with ADHD, 59 of them suffering executive dysfunction, we took the most widely used tests for executive functions in ADHD (Behavior Rating Inventory of Executive Function (BRIEF), Swanson, Noland, and Pelham (SNAP)-IV, and Conners' Parent Rating Scale (CPRS-R)) and applied several methods of test shortening: Item-total correlations from the Classical Test Theory, factor analysis and their subsequent factor loadings, elastic nets, and the Graded Response Model from the Item Response Theory models. Using the parameters or indicators provided by each of these methods, we selected the most discriminative items to develop a brief screening tool. Results: Our results show that different selection methods select different items. More importantly, we found that the shortened tests obtained this way are in general capable of discriminating between patients with and without ADHD. More precisely, all the shortened tests show high sensitivity, but relatively low specificity. Conclusions: Shortened tests can be used for screening purposes without having to administer full test versions.